2005
DOI: 10.1158/0008-5472.can-04-3576
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 by MDM2 Antagonists Can Protect Proliferating Cells from Mitotic Inhibitors

Abstract: Recent studies have shown that activation of cell cycle checkpoints can protect normal proliferating cells from mitotic inhibitors by preventing their entry into mitosis. These studies have used genotoxic agents that act, at least in part, by activation of the p53 pathway. However, genotoxic drugs are known also to have p53-independent activities and could affect the sensitivity of tumor cells to antimitotic agents. Recently, we have developed the first potent and selective small-molecule inhibitors of the p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
176
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(185 citation statements)
references
References 23 publications
6
176
1
2
Order By: Relevance
“…The induction of p53-dependent cell-cycle arrest has an important role in the control of cellular proliferation and may help protect cells against the effects of certain chemotherapeutic agents (Carvajal et al, 2005;Kranz and Dobbelstein, 2006). The induction of polyadenylated mRNAs produced from replication-dependent histone genes following p53-induced G1 cell-cycle arrest may be significant as the polyadenylated histone transcripts have a longer half-life than the normally processed transcripts from the same genes (Kirsh et al, 1989) and are translated in a cell cycle-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of p53-dependent cell-cycle arrest has an important role in the control of cellular proliferation and may help protect cells against the effects of certain chemotherapeutic agents (Carvajal et al, 2005;Kranz and Dobbelstein, 2006). The induction of polyadenylated mRNAs produced from replication-dependent histone genes following p53-induced G1 cell-cycle arrest may be significant as the polyadenylated histone transcripts have a longer half-life than the normally processed transcripts from the same genes (Kirsh et al, 1989) and are translated in a cell cycle-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells with wild-type p53, this results in induction of p53 target genes, cell cycle arrest and apoptosis (Vassilev et al, 2004). In some cases, growth arrest at the G1 and G2 phases of the cell cycle by Nutlin-3a can protect proliferating cells from the cytotoxic effect of mitotic poisons (Carvajal et al, 2005). Previous findings have suggested that Nutlins may offer a new therapeutic option to patients with tumors that express wild-type p53 either as single agent (Vassilev, 2005;Tovar et al, 2005) or as combination therapy (Kojima et al, 2005;Stuhmer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have suggested that Nutlins may offer a new therapeutic option to patients with tumors that express wild-type p53 either as single agent (Vassilev, 2005;Tovar et al, 2005) or as combination therapy (Kojima et al, 2005;Stuhmer et al, 2005). In contrast, tumor cells with mutant p53 are resistant to Nutlin-3a (Carvajal et al, 2005). This would indicate that therapeutic utility of MDM2 antagonists is limited to the treatment of tumors that are wild type for p53.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations